The Role of Conversation in Technology Education - Fox-Turnbull, Wendy (Design and Technology Education: An International Journal, 2010)
This article investigates recent literature in the area of classroom conversation and dialogue with the aim of gaining a better understanding of the role that classroom conversation and dialogue plays in learning. It also investigates literature on the constructivist, collaborative nature of technology education and suggests that to enhance our understanding of how children learn in technology it is necessary to understand the impact that clearly focused conversations of children, amongst themselves and between children and their teachers while undertaking technological practice, has on advancing thinking and understanding. It also suggests that by understanding the full impact of classroom conversation and facilitating its use in the classroom, teachers can greatly enhance learning in technology education. Conversation with and between students allows teachers insight into the impacts of previous and specifically targeted learning experiences on learning in technology. Classroom dialogue can also enhance understanding of how learning occurs in technology and how interaction with peers and teachers advances thinking around technological concepts and components of practice. A related study currently being undertaken investigates the nature of conversation in the primary technology classroom with the aim of facilitating and developing teachers’ understanding to better enhance learning for children in technology education. It is the author’s intention to submit the results of this study to this publication in the future.